Relation of the stage of parasite development in the peripheral blood to prognosis in severe falciparum malaria. - Silamut, K; White, N (1993)
Admission blood films from 72 patients who died of severe falciparum malaria (50 Thai adults, 22 Gambian children) were matched retrospectively for parasitaemia with equal numbers of survivors. The peripheral blood parasites from fatal cases were more mature than those from survivors. Tiny rings (TR) comprised > 50% of parasites in 47/72 (65%) survivors but only 12/72 (17%) of fatal cases (P < 0.001). Parasites containing visible pigment (MTS: mature trophozoites and schizonts) comprised < 20% of the total parasite count in 10/72 (14%) survivors compared with 31/72 (43%) fatal cases (P < 0.001). Of the 39 patients with > 10(4) MTS/microL, 30 (81%) died. These findings were confirmed in a prospective study of 279 adult Thai patients admitted sequentially with acute falciparum malaria. Only 4 of the 19 fatal cases (21%) had > 50% TR, compared with 130 of 260 (50%) survivors, whereas > 20% MTS were found in 10/19 (53%) fatal cases, compared with 28/108 (27%) severe malaria survivors, and 26/155 (17%) patients with moderately severe malaria (P = 0.001). As a predictor of fatal outcome, the finding of either > 10(4) MTS/microL or > 5 x 10(5) parasites/microL in severe malaria had a sensitivity of 90% (95% confidence interval [CI] = 75-97%) and a specificity of 72% (95% CI = 59-86%). These observations are consistent with the hypothesis that a predominance of mature parasites in the peripheral blood reflects a greater sequestered biomass, and thus more severe disease. Simple microscopical assessment of parasite maturity on an admission blood slide provides important pathophysiological and prognostic information in severe falciparum malaria.